THE CRITICAL ANALYSIS ON DIAGNOSIS OF DISSEMINATED INTRAVASCULAR COAGULATION WITH SCREENING TESTS-A SCORING SYSTEM AND RELATED LITERATURE REVIEW - Tang, Bing H. (Journal of Ayub Medical College Abbottabad, 2007)
Background: The aim of this study is to assess confidence in the diagnosis of Disseminated Intravascular Coagulation (DIC); to evaluate the clinical significance of the haemostatic tests; to disclose any respective associations of such tests with patients’ prognosis; and to review the related literature. It is a retrospective case series study in Changhua Christian Hospital, Taiwan. Methods: Ninety-four patients’ data were analyzed. A scoring system was constructed retrospectively. Results: Hypotheses were postulated and proved. Each patient had a minimal score of 5, whereas those patients who had reached (increased) their scores were to the full or even over the maximal level (6 or 9) respectively. There was almost no correlation between age and Prothrombin Time (PT). The correlation between age and platelet count, and that between age and fibrinogen were positively minor respectively, whereas that of Activated Partial Thromboplastin Time (APTT) was +0.208. The correlations between APTT and PT, platelet count, fibrinogen respectively were significant. About 45.67% of patients had plasma fibrinogen >200 mg/dL, while 22.23% had <100 mg/dL. A paradox was observed. The finding of such a limited package of the screening tests was discussed. Related literature with regard to the clinical significance and pitfalls, as well as limitations and strengths of these haemostatic tests were reviewed and evaluated. Conclusion: There are 14 points of impression with clinical significance outlined. Keywords: DIC, Surgical Intensive Care Unit, Laboratory diagnosis, Haemostatic test, Screening test.